Numerical study on restraints effects in massive foundation slabs - Klemczak, Barbara (2017)
The aim of the presented study is to simulate the restrained stresses in early age massive foundation slabs. The character of self-induced stresses related to internal restraints resulting from inhomogeneous distribution of thermal-humidity fields as well as restraint stresses related to limitation of structure deformations freedom are described in the article. The combined thermal and both autogenous and drying shrinkage effects are considered. The presented numerical study on the above mentioned effects are conducted with the use of original numerical model. The distribution and the magnitude of stresses induced by hydration temperature and shrinkage are computed, both in heating and curing phase of concrete curing. The special attention is paid to the externally restraint stresses depending strongly on contact layer between the slab and subsoil. Finally, the total restraint stresses are computed for slabs with different thickness.